Age-Related Differences in the Expression of Most Relevant Mediators of SARS-CoV-2 Infection in Human Respiratory and Gastrointestinal Tract - Berni Canani, Roberto; Comegna, Marika; Paparo, Lorella; Cernera, Gustavo; Bruno, Cristina; Strisciuglio, Caterina; Zollo, Immacolata; Gravina, Antonietta Gerarda; Miele, Erasmo; Cantone, Elena; Gennarelli, Nicola; Nocerino, Rita; et al. (Frontiers in Pediatrics, 2021)
Background: Clinical features of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection seem to differ in children compared to that in adults. It has been hypothesized that the lower clinical severity in children could be influenced by differential expression of the main host functional receptor to SARS-CoV-2, the angiotensin-converting enzyme 2 (ACE2), but data are still conflicting. To explore the origin of age-dependent clinical features of coronavirus disease 2019 (COVID-19), we comparatively evaluated the expression in children and adult subjects of the most relevant mediators of the SARS-CoV-2 infection: ACE2, angiotensin-converting enzyme 1 (ACE1), transmembrane serine protease-2 (TMPRSS2), and neuropilin-1 (NRP1), at upper respiratory tract and small intestine level. Methods: The expression of ACE2, ACE1, TMPRSS2, and NRP1 in nasal epithelium and in small intestine epithelium was investigated by quantitative real-time PCR analysis. Results: We found no differences in ACE2, ACE1, and TMPRSS2 expression in the nasal epithelium comparing children and adult subjects. In contrast, nasal epithelium NRP1 expression was lower in children compared to that in adults. Intestinal ACE2 expression was higher in children compared to that in adults, whereas intestinal ACE1 expression was higher in adults. Intestinal TMPRSS2 and NRP1 expression was similar comparing children and adult subjects. Conclusions: The lower severity of SARS-CoV-2 infection observed in children may be due to a different expression of nasal NRP1, that promotes the virus interaction with ACE2. However, the common findings of intestinal symptoms in children could be due to a higher expression of ACE2 at this level. The insights from these data will be useful in determining the treatment policies and preventive measures for COVID-19.